The Influence of Fintech P2P Lending on Islamic Bank Financing (IQTISHADIA, 2025)
The rise of financial technology (fintech) has disrupted traditional banking systems, introducing both challenges and opportunities. While fintech financing has resulted in a substitution effect that diminishes banking value, it also complements the banking sector by leveraging technology to improve financial services. This study investigates the impact of fintech peer-to-peer (P2P) on Islamic banking financing and examines the role of financial inclusion in moderating this relationship. Using panel data regression across Indonesian regions from 2021 to 2023 with a fixed-effects model, the findings reveal that fintech P2P lending, bank assets, and bank deposits positively and significantly influence Islamic bank financing. However, financial inclusion and its interaction with fintech P2P lending exhibit a negative and significant effect, suggesting that an increase in Islamic bank branches, as a proxy of financial inclusion, reduces Islamic bank financing and weakens the link between fintech P2P lending and Islamic bank financing. These results highlight the need for an innovative approach to financial inclusion, such as enhancing digital financial services, while urging practitioners and regulators to align fintech adoption with inclusive financial strategies to optimize its impact.